A systematic review of scalable hardware architectures for pattern matching in network security. (June 2021) - Imran, Malik; Bashir, Faisal; Jafri, Atif Raza; Rashid, Muhammad; ul Islam, Muhammad Najam
Highlights: A systematic literature review for scalable hardware architectures. Classification of pattern matching techniques in network security. A comparative analysis of various algorithms, techniques and architectures. Performance comparison in terms of various design parameters. Identification of emerging trends and design challenges. Abstract: Pattern matching algorithms and techniques are extensively deployed in a network intrusion detection system. A plethora of scalable pattern matching hardware architectures exist with several design parameters, and therefore, a systematic literature review is essential. This article classifies the most recent research studies, concerning to the scalable hardware implementations of pattern matching algorithms and techniques, through a systematic literature review. As a result, 49 research studies are selected. The selected research studies are then classified into string matching and regular expression matching algorithms and also analyzed in terms of single character and multi-characters pattern matching. Consequently, a comparative analysis of various algorithms, techniques, and architectures in the light of several design parameters (such as throughput, area, power, frequency, rule set, total signatures etc.) is provided. Based on the comparative analysis, some emerging trends and design challenges are highlighted. Graphical abstract: Image, graphical abstract